Development of a systematic method in lean tool selection for automotive industry - Anvari, Alireza (2012)
The efficiency and effectiveness of lean practices have always been the major concerns for manufacturers. The current research highlighted the role of lean tools on leanness level in automotive industry. The main problem of automotive industry is its focus on process Kaizen instead of flow Kaizen. As a matter of fact, selecting and applying lean tools should comprehensively and holistically be considered in the principles and concepts within a systematic approach. Therefore, developing a systematic method to facilitate lean tool selection more precisely is required in this industry. The proposed method was developed within a five step group decision making procedure to reach the desired aims. To fulfill the objectives of this study, a variety of Multi Criteria Decision Making (MCDM) and Data Envelopment Analysis (DEA) methods were employed, also the designed software used MATLA to experience the systematic lean tool selection. The results of the study displayed that each of the lean attributes (lead time, cost, defect,and value) did affect the tool selection among companies. Furthermore, based on the results of the current research, a modified VIKOR method was developed. It is noteworthy to state that the suggested model for lean tool selection (defined in software) was validated within a panel of experts and companies indicating the effectiveness and usefulness of the model. There is the likelihood that this new developed method may enhance the competence and qualifications of practitioners to spot the possible problems and find solutions once the alternatives (lean tools) possess their own exclusive criteria. The developed software probably assists manufacturers in applying the systematic lean tool selection. Based on the systematic features of this algorithm, the efficiency and effectiveness of the model in presenting optimizing techniques for lean tool selection with the automotive industry seems reasonable and useful. According to the findings of this study, lean practitioners can choose tools systematically via this recommended method in a dual approach i.e. attribute based (individually) and/or leanness based (wholly). The current research paves the path to propose a generalized method that makes it possible for a user to holistically recognize and evaluate the tools influencing the application of lean manufacturing developments. Consequently, it should be borne in mind that taking tools performance into consideration while implementing lean practices has been of a great benefit for companies.